L’information-people, entre rhétorique du cas particulier et récits de l’intimité - Annik Dubied (Communication)
This paper begins by presenting a five-part definition of celebrity news. It then focuses on three major issues surrounding this subject, and upon which sociology can reflect. First, the link between celebrity and individualism is examined, followed by the link between celebrity and the exposure of private life in the public sphere; and finally, an analytical matrix of celebrity news, extracted from its own definition, is outlined.